Application of body composition zones in boys with nonalcoholic fatty liver disease - Minhye Choi; Seonhwa Lee; Sun Hwan Bae; Sochung Chung (Korean Society of Pediatric Endocrinology, 2019)
Purpose Screening nonalcoholic fatty liver disease (NAFLD) by body mass index (BMI) as a single surrogate measure for obesity has limitations. We suggest considering body composition zones by drawing a body composition chart composed of body composition indices, including BMI and percent body fat (PBF), to visualize the risk of NAFLD in obese children and adolescents. Methods Thirty-eight boys diagnosed with NAFLD were selected retrospectively from patients who visited Konkuk University Medical Center from 2006 to 2015. They had gone through body composition analysis by bioelectrical impedance analysis (BIA), and biochemical analyses, including a liver function test (LFT) and lipid panel, were performed. Fat-free mass index (FFMI) and fat mass index (FMI) were calculated from body composition analysis and height. We plotted FFMI and FMI of patients on a body composition chart and classified the patients into zones A to D. In addition, we analyzed the correlations between LFT, lipid panel, and body composition indices. Results Thirty-three of 38 boys (86.8%) were located in zone C, corresponding to high BMI and PBF. Four boys (10.5%) were located in zone D, which correlates with sarcopenic obesity. One boy located in zone B was a muscular adolescent. Alanine aminotransferase level was positively correlated with PBF, FMI, and BMI z-score. Conclusions Body composition zones on a body composition chart might be useful in risk assessment in obesity-related diseases such as NAFLD. Zones on a body composition chart could have practical applications, especially in sarcopenic obese children and adolescents.